Foresight beats hindsight: The neural correlates underlying motor preparation in the pro‐/anti‐cue paradigm. Issue 5 (30th March 2017) - Emmerling, Franziska; Duecker, Felix; de Graaf, Tom A.; Schuhmann, Teresa; Adam, Jos J.; Sack, Alexander T.
Abstract: Background: Human motor behaviors are characterized by both, reactive and proactive mechanisms. Yet, studies investigating the neural correlates of motor behavior almost exclusively focused on reactive motor processes. Here, we employed the pro‐/anti‐cue motor preparation paradigm to systematically study proactive motor control in an imaging environment. In this paradigm, either pro‐ or anti‐cues are presented in a blocked design. Four fingers (two from each hand) are mapped onto four visual target locations. Visual targets require a speeded response by one corresponding finger, but, most importantly, they are preceded by visual cues that are congruent ("pro‐cue"), incongruent ("anti‐cue"), or neutral with respect to the responding hand. With short cue‐target intervals, congruence effects are based on automatic motor priming of the correct hand (in case of pro‐cues) or incorrect hand (in case of anti‐cues), generating, respectively, reaction time benefits or reaction time costs relative to the neutral‐cue. With longer cue‐target intervals, slower top‐down processes become effective, transforming early anti‐cue interference into late anti‐cue facilitation. Methods: We adapted this paradigm to be compatible with neuroimaging, tested and validated it behaviorally—both inside and outside the imaging environment—and implemented it in a whole‐brain functional magnetic resonance imaging study. Results and Conclusion: Our imaging results indicate that pro‐cues elicited much less neural activation than did anti‐cues, the latter recruiting well‐known cognitive top‐down networks related to attention, response inhibition, and error monitoring/signaling, thereby revealing high‐level influences on proactive motor processes. Abstract : In this study, we investigated the neural mechanisms underlying motor preparation in the pro‐/anti‐cue paradigm.